Strategi Pengembangan Bahan Ajar Berbasis Kurikulum Merdeka dalam Pembelajaran Abad 21 - Astrid Kurniawati; Delvi Hulopi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The Merdeka Curriculum demands the development of teaching materials that are adaptive, contextual, and relevant to the demands of 21st-century learning. This article aims to examine the strategy for developing teaching materials based on the Merdeka Curriculum that can support the strengthening of 21st-century competencies, such as critical thinking, creativity, collaboration, and digital literacy. The method used is a literature review of various studies related to the Merdeka Curriculum, teaching material development, and 21st-century learning. The findings show that effective teaching material development must consider the integration of local context, the use of digital technology, and project- and problem-based approaches. In addition, it is also important to conduct continuous reflection and evaluation in the teaching material development process. With the right strategy, teaching materials based on the Merdeka Curriculum can become a key tool in creating meaningful, flexible learning that aligns with the needs of 21st-century learners. Through the implementation of this strategy, it is hoped that a more effective learning process that aligns with the times can be created.